1995
DOI: 10.1364/ao.34.003240
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive dual-beam absorption and gain spectroscopy: applications for near-infrared and visible diode laser sensors

Abstract: A dual-beam detection strategy with automatic balancing is described for ultrasensitive spectroscopy. Absorbances of 2 × 10(-7) Hz(-½) in free-space configurations and 5 × 10(-6) Hz(-½) in fiber-coupled configurations are demonstrated. With the dual-beam technique, atmospherically broadened absorption transitions may be resolved with InGaAsP, AlGaAs, and AlGaInP single-longitudinal-mode diode lasers. Applications to trace measurements of NO(2), O(2), and H(2)O are described by the use of simple, inexpensive la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(61 citation statements)
references
References 19 publications
1
60
0
Order By: Relevance
“…[1][2][3][4] The principles are straightforward: Gas molecules absorb energy at specific wavelengths in the electromagnetic spectrum. At wavelengths slightly different than these absorption lines, there is essentially no absorption.…”
Section: Measurement Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] The principles are straightforward: Gas molecules absorb energy at specific wavelengths in the electromagnetic spectrum. At wavelengths slightly different than these absorption lines, there is essentially no absorption.…”
Section: Measurement Approachmentioning
confidence: 99%
“…This transmission system serves local distribution companies that operate some 500-1000 gate stations supplying roughly 132,000 surface metering and pressure regulation sites stationed along 1,000,000 miles of distribution pipeline terminating at 61,000,000 end-user customer meters. 1 Maintaining the security and integrity of this system is a continual process of searching for, locating, and repairing leaks.…”
Section: Introductionmentioning
confidence: 99%
“…Laser Sources or LEDs Allen et al 48 and Sonnenfroh and Allen 49 reported the application of single-longitudinal-mode, room-temperature semiconductor lasers operating in the visible and near IR spectra to in situ monitoring of NO 2 . They reported a system design that uses the relatively new balanced ratiometric detector, a novel electronic laser noise-canceling technique.…”
Section: Systems Using Visible/near-ir Radiationmentioning
confidence: 99%
“…For robust implementation, it often uses Distributed Feedback Lasers (DFB) to address various overtone bands and incorporates Wavelength Modulation Spectrometry (WMS) for reduction of noise [16][17][18][19][20]. Although this technique is versatile and regularly used for detection of a number of species under various conditions [12][13][14][15][21][22][23][24][25][26][27], its detectability is not yet sufficient for in-situ detection of NO [28][29][30][31][32][33][34], primarily caused by a combination of low transition probabilities of the overtone bands in 3 the infrared (IR) region and a lack of reliable diode lasers producing light in the wavelength regions of these bands. In addition, the overtone bands are susceptible to spectroscopic interferences from concomitant species, which can hamper quantitative assessments.…”
Section: Introductionmentioning
confidence: 99%